Research on strategies for reducing the irritability of potassium cocoyl glycinate in cleansing - Anli Peng; Jialei Yan; Jianming Wang; Jingru Qian; Yao Qin; Yaxin Zhang; Tingzhi Zhang (Journal of Dermatologic Science and Cosmetic Technology, 2024)
Background: Potassium cocoyl glycinate, a kind of amino acid surfactant, is widely used as major component for facial cleansing. However, the interaction between surfactants and compounds in the stratum corneum has been suggested as a contributing factor to their potential skin irritancy. Objective: This study aimed to the effects of adding surfactants, polymers, lipids and active substances on diminishing skin irritation caused by potassium cocoyl glycinate. Materials and methods: Zein test and Hemolysis test enabled the identification of irritation to proteins and cells in the studied binary systems. The critical micelle concentration (CMC) was evaluated by the surface tension method. The power of the analyzed polymers to diminish irritation of potassium cocoyl glycinate was represented by the reduction rate. Results: (1) Amphoteric surfactants and nonionic surfactants are effective at reducing the irritation of potassium cocoyl glycinate in some cases by reducing CMC; (2) Addition of polymers to the potassium cocoyl glycinate solutions improves its safety of use. Hydroxypropyl methylcellulose could reduce the irritation by 88.63%; (3) Combining most lipids can assist in declining the irritation, Lppg-28-Buteth-35 could inhibit the irritation of red blood cells by 16.52%; (4) The effects of active substances varied, hydrolyzed sodium hyaluronate results in a significant reduction in irritation to cells. Conclusion: In facial cleansers based on potassium cocoyl glycinate, supplying co-surfactant, polymers, lipids and active substances can reduce the irritation to some extent, however, the effects are various.